2015
DOI: 10.1097/brs.0000000000000952
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Curve Progression in Idiopathic Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 14 publications
4
34
1
Order By: Relevance
“…Similar findings were also reported by Sitoula et al [24] who retrospectively studied a sample of 161 patients from initial diagnosis until reaching skeletal maturity, curve progression to ≥50˚, or spinal fusion. Fifty-one percent of the patients in the study were braced and half of them progressed at endpoint.…”
Section: Initial Cobb Anglesupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were also reported by Sitoula et al [24] who retrospectively studied a sample of 161 patients from initial diagnosis until reaching skeletal maturity, curve progression to ≥50˚, or spinal fusion. Fifty-one percent of the patients in the study were braced and half of them progressed at endpoint.…”
Section: Initial Cobb Anglesupporting
confidence: 88%
“…Another study by Whitaker et al [37] looked specifically at the value of bracing patients that are 40˚or more and found that of the Risser 0 patients that are >40˚, 84% had surgery or were >50˚at the end of treatment. Sitoula et al [24] found that 100% of the patients with curves ≥40˚and Risser ≤4 progress to the surgery threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate prediction of which AIS patients will experience curve progression is dependent on the clinician's ability to interpret the remaining growth potential. At initial presentation, the severity of the deformity measured by the Cobb angle and growth rate can provide useful information regarding the likely future curve behavior [ 5 21 ]. Many radiographic parameters exist to predict growth but have known limitations, including poor prediction of PHV for the timing of brace treatment [ 22 23 24 25 26 ], concerns with inter-observer reliability and complexity [ 27 28 29 ], and the cumbersome nature of using them in a busy clinical setting [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Determining a child's remaining skeletal growth is crucial for the management of adolescent idiopathic scoliosis (AIS) [ 1 2 3 ]. This is particularly important for brace treatment because the prompt initiation of this management approach can reduce the number of AIS patients undergoing surgery [ 4 5 6 ]. Generally, the goal of a bracing treatment is to prevent a patient from reaching the commonly described surgical threshold of >50°.…”
Section: Introductionmentioning
confidence: 99%
“…It identifies 8 stages of progression from ‘juvenile slow’ to ‘mature’. This classification compares the Cobb angle and digital skeletal age to predict the likelihood of curve progression [ 17 , 18 ].…”
Section: Natural Historymentioning
confidence: 99%